Les subalternes iraniennes ont-elles besoin d’être sauvées ? Entretien avec Azadeh Kian - Lucia Direnberger; Sahar Aurore Saeidnia (Genre, Sexualité et Société)
In this interview, we cover the significant research career of Azadeh Kian, who, over thirty years, has developed a sociology of gender, class and ethnic relations in contemporary Iran. Her reflection on the interweaving of various systems of social hierarchisation has led to the analysis of the identity strategies of Iranian women, mothers, wives, citizens and workers; their politicisation; and their practices of resistance. Her research deconstructs the conception of women in Iran as belonging to a homogeneous and unified category. On the contrary, Azadeh Kian underlines their agentivity and their power relations.